Penyusunan Rencana Pelaksanaan Pembelajaran PPKn dengan Pendekatan Contextual Teaching Learning di Sekolah Dasar - Servista Bukit (Lembaga Riset Ilmiah, 2022)
The purpose of this study is to describe how teachers prepare Learning Implementation Plans for PPKn lesson content with a Contextual Teaching Learning (CTL) approach including how teachers formulate learning objectives, develop learning steps, and design learning assessments with a CTL approach. The research method uses descriptive qualitative research. The subjects of this research are high school teachers, principals, and students. Data collection techniques using interviews, observation, and documentation. Test the validity of the data using triangulation of sources and techniques. Based on the results of research at SD Negeri 101835 Sibolangit, it was found that in formulating learning objectives, the teacher first designed the Competency Achievement Indicators (GPA) based on KI and KD, learning objectives were written by taking into account the elements of Audience, Behavior, Condition, and Degree. In compiling the learning steps, the teacher integrates the components in the CTL approach including constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. In designing the assessment, the teacher pays attention to aspects of authentic assessment including the assessment of attitudes, knowledge, and skills that are tailored to the learning objectives.